2006
DOI: 10.1121/1.2159430
|View full text |Cite
|
Sign up to set email alerts
|

Induced loudness reduction as a function of exposure time and signal frequency

Abstract: Induced loudness reduction (ILR) is the decline in the loudness of a weaker tone induced by a preceding stronger tone. In this study we investigate how ILR depends on exposure time and signal frequency. For 12 listeners, successive magnitude estimation was used to measure the loudness of 70-dB-SPL test tones, presented with and without preceding 80-dB-SPL inducer tones at the same frequency. Experiment 1 measured the evolution of ILR over time at 0.5 kHz. The results suggest that ILR may begin after a single i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…This possibility requires careful further examination, but is supported by the lower overall ILR (about 8 dB) found in studies using modified procedures (Epstein and Gifford, 2006;Wagner and Scharf, 2006). Wagner and Scharf (2006) found that ILR is fairly constant across the frequencies 0.5-8 kHz when the inducer and test tone are at the same frequency. This supports the idea that ILR is a pervasive effect and not just something that occurs within a very limited bandwidth.…”
Section: Mapesmentioning
confidence: 94%
See 2 more Smart Citations
“…This possibility requires careful further examination, but is supported by the lower overall ILR (about 8 dB) found in studies using modified procedures (Epstein and Gifford, 2006;Wagner and Scharf, 2006). Wagner and Scharf (2006) found that ILR is fairly constant across the frequencies 0.5-8 kHz when the inducer and test tone are at the same frequency. This supports the idea that ILR is a pervasive effect and not just something that occurs within a very limited bandwidth.…”
Section: Mapesmentioning
confidence: 94%
“…Although some studies have used direct magnitude estimation to assess ILR (e.g., Wagner and Scharf, 2006), loudness matching is the most common procedure. Loudness matches are made between two sounds, one that is affected by ILR and the other carefully selected to avoid the effects of ILR.…”
Section: How Is Ilr Measured?mentioning
confidence: 99%
See 1 more Smart Citation
“…It is, however, difficult to model the effects of ILR on a particular experiment, because of the dependence on several factors (see Epstein, 2007, for a review), including (1) tone levels (Mapes-Riordan & Yost, 1999), (2) frequency separation between inducer and test tones (Marks, 1994), (3) durations of inducer and test tones (Nieder, Buus, Florentine, & Scharf, 2003), (4) time separation between inducer and test tones (Arieh & Marks, 2003), (5) number of exposures to inducers (Arieh et al, 2005), and (6) individual differences (Epstein & Gifford, 2006;Wagner & Scharf, 2006).…”
mentioning
confidence: 99%
“…Second, ILR transcends a particular measurement method, being observed in loudness matching (Mapes-Riordan & Yost, 1999;Nieder, Buus, Florentine, & Scharf, 2003), magnitude estimation (Marks, 1988(Marks, , 1994Wagner & Scharf, 2006), judgments of loudness differences (Parker & Schneider, 1994;Schneider & Parker, 1990), and response time (Arieh & Marks, 2003a). Third, ILR is fast to set in but slow to dissipate: A significant amount of ILR was measured 225 msec after the onset of the inducer and was still evident dozen of seconds later (Arieh, Kelly, & Marks, 2005;Arieh & Marks, 2003b;Wagner & Scharf, 2006). This time course is similar to processes of peripheral sensory adaptation in other modalities-such as, in vision, processes of rapid light adaptation but slower dark adaptation (e.g., Mahroo & Lamb, 2004).…”
mentioning
confidence: 99%